A political spectator sport or policy priority? A review of sport, physical activity and public mental health policy. Issue 4 (1st October 2016) - Smith, Andy; Jones, Jon; Houghton, Laura; Duffell, Tom
ABSTRACT: In the context of policy and political claims about the benefits of encouraging participation in sport, physical activity (PA) and exercise for physical and mental health, and for improving the effectiveness of prevention, early intervention and treatment services for people with mental illness, this article provides, for the first time, a critical overview of policy related to community sport, PA and public mental health (PMH). Focusing on England, the article analyses 18 key policy documents published between 1995 and May 2016. We explain that the promotion of PMH and prevention and treatment of mental illness through participation in PA or exercise, as a formal goal of mental health policy, has been generally absent from the public health policy landscape. Until very recently, PMH and illness are also shown to be neglected as core priorities of community sport and PA policy in England. Even where PMH is discussed explicitly in national policy, a clear definition of specific and measurable goals, which can be used to determine the efficacy, effectiveness and comparative effectiveness of policy in addressing PMH outcomes, is notably absent. The article concludes by suggesting that, at present, the improvement of PMH and tackling mental illness through community sport and PA appears to be more of a political spectator sport than a clearly thought-out, sustained and long-term commitment of public policy.